The Influence of Digitalization on the Innovative Strategy of the Industrial Enterprises Development in the Context of Ensuring Economic Security - Грубляк, Оксана Михайлівна (My University, 2023)
The purpose of the article is to study the impact of digitalization on the innovative strategy of the enterprise development in the context of ensuring economic security. Within the article, peculiarities of the digitalization development in Ukraine are examined. The main obstacles that hold back the development of innovative technologies and digital platforms in Ukraine are identified. The problems of the country's industrial development and the difficulties of implementing the principles of the digital economy in the existing conditions are substantiated. It was determined that industrial development of the country is decreasing, which leads to a low level of digitalization and innovative development of industrial productions and reduces their level of economic security and competitiveness. The impact of digitization on the innovative development of industrial enterprises was considered based on the calculation of efficiency indicators of the innovative activity for selected systems of the production process. Based on the calculations made using the correlation-regression analysis, the influence of the selected factors on the resulting indicator was determined. The areas that influence slowing down of the digital development process of industrial enterprises are singled out.
Keywords: digitalization, digital economy, digital transformations, strategy of innovative development, innovative provision, innovative activity, industrial enterprises, economic security